Implementation of Smart Co-Housing Concept in Middle-Aged Adult Community in Indonesia - Try Ramadhan; Dindha Nirmalasari; Mutiara Ningrum; Beatricia Beatricia; Heince Andre Maahury (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT : The population of productive age will reach 70% in 2020-2030, while the remaining 30% is unproductive population (under 15 years and above 65 years). The increasing number of population will affect on increasing housing needs, whereas if viewed from the availability of land, it will be difficult to realize a private housing that will required land is large enough for each family. When faced with other phenomena, the productive age composition is filled by a year old aged of 35-60 years and dominated by a millennials generation. This generation is very open and accustomed to the use of technology in daily life. The proximity of millennial generation with technology will revolutionize the way of human life, especially how to settle to influence the growth of housing and urban in indonesia. Therefore, with regard to the problem of increasing housing needs due to the explosion of population in Indonesia, if faced with demands of technological demand as a lifestyle of millennials, the concept of ' smart co-housing ' which is the concept of a decent and integrated residential housing that can consist of several families. Smart co-housing contains two concepts of house concept, which are smart house and shared house. Smart house is a concept of houses that apply technology application and directed into the eco-friendly housing because there is control of energy consumption. Meanwhile, house sharing is a residential concept combining of multiple families with the sharing of private and public spaces as a communal spaces. This research uses a descriptive method that examines the concept of smart co-housing to make a description of the concept systematically later compared to similar phenomena that have occurred in other countries (comparative study) to determine the potential and challenge of the implications of this housing concept in Indonesia. The results of this study indicate that the smart co-housing concept can be applied in Indonesia as a solution of increasing housing needs for millennials in middle adulthood, in terms of economic, social, and environmental aspects.Keywords : Demographic bonuses, co-housing, middle-aged adult, smart housing